Desempenho organizacional de operadora de planos de saúde suplementar no Brasil: estudo de caso de uma cooperativa médica - Carmo, Eduardo do (2016)
The increased participation of the private sector in the field of health services has gained prominence since the 1980s. The Brazilian government, from the second half of the 1990s, has redesigned its role in breaking the state monopoly and allowed the expansion of private activity in various fields of economy, becoming a mediator and regulator. In this context, the establishment of the National Health Agency (ANS), in January 2000, marked a stage of sector regulation, which went through several transformations that led to the increase in costs and decrease in the number of Health Plans Operators (OPS) in activity. The concern with actions aimed at maintaining the financial health of these companies is therefore the starting point of this study. This is a case study that aims to investigate the influence of organizational and environmental factors, from the perspective of the managers of a small cooperative medical work (called OPX), which contributed to the construction of higher organizational performance, shown in a previous study. The investigation is based on four analytical categories that are related to organizational performance: organizational culture, organizational structure, strategic management and external environment. Data were collected from three sources of evidence: documents, direct observation and semi-structured interviews with the participation of key managers of the organization. Data were analyzed using Content Analysis method. Elements that characterize the organizational culture of the cooperative were identified. Regarding the type of structure, it is specialized professional bureaucracy. The formal process of strategic management are not effectively used, but operational control tools proved rigid . And about the external environment were relevant competition, regulation, the judiciary and the economy. All of them, to some extent, influenced the organization's performance. It was not found any other feature for defining new category that could help answer the research question.